Immunological Efficacy of Tenofovir Disproxil Fumarate-Containing Regimens in Patients With HIV-HBV Coinfection: A Systematic Review and Meta-Analysis - Jiang, Taiyi; Su, Bin; Song, Ting; Zhu, Zhiqiang; Xia, Wei; Dai, Lili; Wang, Wen; Zhang, Tong; Wu, Hao (Frontiers in Pharmacology, 2019)
Background Hepatitis B virus (HBV) coinfection is common in HIV-positive patients. HIV infection modifies the natural course of HBV infection, leading to a faster progression of liver-related morbidity and mortality than is observed in HBV mono-infected patients. This systematic review and meta-analysis evaluates the current clinical evidence regarding the use of oral tenofovir disproxil fumarate (TDF)-based treatments in patients coinfected with HIV and HBV. Methods We performed a comprehensive literature search in PubMed and Web of Science. Supplementary searches were conducted in Google Scholar and Clinicaltrials.gov. We conducted a random effects meta-analysis using the event rate (ER) to estimate the incidence of HBV seroconversion. A subgroup meta-analysis was performed to assess the moderate effects of demographic and disease-related variables on HBsAg loss. This review is registered in the PROSPERO database (CRD42018092379). Results We included 11 studies in the review. The immunological effects of oral TDF-based Pre-exposure prophylaxis (PrEP) treatment in patients with HIV-HBV coinfection were 0.249 for HBeAg loss, 0.237 for HBeAg conversion, 0.073 for HBsAg loss, and 0.055 for HBsAg conversion. The factors associated with HBsAg loss were the baseline HBV viral load, participant’s location, and a history of exposure to lamivudine/emtricitabine (3TC/FTC) (all p < 0.05). A trend toward a negative relationship between the baseline CD4+ T-cell count and HBsAg loss was observed (p = 0.078). Conclusion This systematic review and meta-analysis demonstrated that TDF-containing regimens are effective at stimulating HBeAg loss (24.9%), HBeAg conversion (23.7%), HBsAg loss (7.3%) and HBsAg conversion (5.5%) in HIV-HBV coinfected patients. The moderator analysis showed that HBV viral load, the location of participants, and prior exposure to 3TC/FTC are factors associated with HBsAg loss. Asian ethnicity, prior exposure to 3TC and a nondetectable baseline HBV viral load are associated with lower odds of HBsAg loss. Well-designed prospective cohort studies and randomized controlled trials (RCTs) with large sample sizes are required for the investigation of potential predictors and biological markers associated with strategies for achieving HBV remission in patients with HIV-HBV coinfection, which is a matter of considerable importance to clinicians and those responsible for health policies.